The Role of Place Identity in Planning Heritage Tourism - Nurlisa Ginting; N. Vinky Rahman; Subhilhar Subhilhar; Julaihi Wahid (The Indonesian Journal of Planning and Development, 2018)
Spatial planning can improve one’s quality of life by enhancing the environmental quality and its potential. Thus, the application of the concept of identity into the planning process is essential in emphasizing the significance of a place, especially in heritage tourism area, where tourist satisfaction is obtained from the tourism objects peculiarities that become the place identity. However, similar studies are still limited so that this study will contribute to filling the gaps. This study is conducted in Maimoon Palace District, a historic area in Medan. This study aims to examine the application of the concept of spatial planning based on the area identity. A qualitative method is used to collect the data about spatial planning elements in the area. The findings indicate that the existing spatial planning has already contained the place identity. However, many problems in spatial planning elements still cause a chaotic view of the area. Therefore, the government should improve the area not only by improving the physical quality but also increasing tourist satisfaction to enhance tourism attractiveness.